2011
DOI: 10.1002/hep.24539
|View full text |Cite|
|
Sign up to set email alerts
|

Role of cyclophilin B in tumorigenesis and cisplatin resistance in hepatocellular carcinoma in humans

Abstract: Cyclophilin B (CypB) performs diverse roles in living cells, but its role in hepatocellular carcinoma (HCC) is largely unclear. To reveal its role in HCC, we investigated the induction of CypB under hypoxia and its functions in tumor cells in vitro and in vivo. Here, we demonstrated that hypoxia-inducible factor 1a (HIF-1a) induces CypB under hypoxia. Interestingly, CypB protected tumor cells, even p53-defective HCC cells, against hypoxiaand cisplatin-induced apoptosis. Furthermore, it regulated the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 38 publications
5
60
0
Order By: Relevance
“…This is inconsistent with the results of a previous report showing that HIF-1a transcriptionally upregulates CypB under hypoxia. 16 Thus, it is possible that hypoxia-mediated CypB gene induction is due, at least in part, to HIF-1a activation. However, under the conditions employed in this study, a site-directed mutagenesis in the ATF6 binding site prevented hypoxia-induced upregulation of CypB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is inconsistent with the results of a previous report showing that HIF-1a transcriptionally upregulates CypB under hypoxia. 16 Thus, it is possible that hypoxia-mediated CypB gene induction is due, at least in part, to HIF-1a activation. However, under the conditions employed in this study, a site-directed mutagenesis in the ATF6 binding site prevented hypoxia-induced upregulation of CypB.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence microscopy was performed as described previously. 16 Images were taken using the laser-scanning confocal microscope. For quantification, cells for each condition were analyzed in three sets.…”
Section: Methodsmentioning
confidence: 99%
“…Although the proteasome pathway rapidly degrades HIF-1a under normoxia, this protein is stable under hypoxia, where it translocates to the nucleus and binds to hypoxia response elements (HREs) within the promoter of its target genes. Significant evidence indicates that HIF-1a plays an important role in the resistance to chemotherapy of hepatocellular carcinoma (12,13). Hence, inhibition of the HIF-1a pathway is a promising approach for the treatment of hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 7 of the downregulated proteins in the A549 cells were identified by MS, and with the exception of MST, their downregulation favored the anti-tumor activity of Umb. Cyclophilin B is a ubiquitously expressed protein in normal cells and tissues, but protects cancer cells against apoptosis induced by cisplatin, hypoxia and oxidative stresses (26). The protein increases tumor growth, angiogenesis and resistance to therapy (26).…”
Section: Discussionmentioning
confidence: 99%